the Evaluasi Efektivitas Antidepresan Mnyak Atsiri Kayu Cendana (Santalum album L.) Terhadap Mencit Jantan Putih (Mus musculus): EFEKTIVITAS ANTIDEPRESAN - Sundhari, Ade (Institut Teknologi dan Kesehatan Bintang Persada, 2025)
Sandalwood contains essential oils with high abundance of ?-santanol and ?-santanol which can provide antidepressant effectiveness. The purpose of this study was to determine whether sandalwood essential oil (Santalum album L.) can provide antidepressant effectiveness to white male mice (Mus musculus). This research method is a laboratory experiment with a Post Test Control Group Design research design. The antidepressant tests used were TST (Tail Suspention Test) as a stress induction, (FST) Forced Swim Test to test antidepressant potential and Immobility time to determine changes in mouse behavior. CMC Na 0.5% as a negative control and Amitriptyline tablets as a positive control. The results obtained were an average immobility time in the negative control for 8.19 minutes, a positive control for 7.11 minutes and sandalwood essential oil for 6.14 minutes. The results of the overall data analysis were normally distributed using Shapiro-Wilk in the normality test and the overall data was homogeneous with the Levene Statistic test in the homogeneity test, so it was feasible to continue with the One Way ANOVA test. The results of the One Way ANOVA test obtained a p-value of 0.01 <0.05, which means that there is a significant difference in the immobility value of each variable, so it can be concluded that H0 is rejected. Study shows that sandalwood essential oil has significant antidepressant activity. Keywords: sandalwood, essential oil, antidepressant, immobility time